Proposed upgrading handicraft Kedah Gallery at Lot 1416,KM10 Jalan Hutan Kampong, Alor Star Kedah Darul Aman / Zarithnurlissa Zuhirizan - Zuhirizan, Zarithnurlissa (Faculty of Architecture, Planning and Surveying, Universiti Teknologi MARA, 2012)
This project is proposed upgrading Kedah Handicraft located at lot 1416, km. 10, Jalan Hutan Kampong 06200 Kepala Batas, Alor Setar Kedah Darul Aman. Lack of manpower. Young people today are not interested in handicrafts. The aim of the project is to help entrepreneur promote their produced products. This to show handicraft image. General issue of this project are to promote handicraft products and culture Malaysians, is part One Malaysia, maintain the traditional handicraft among Malaysia. Achieve the vision 2020. Lack of manpower. Young people today are not interested in handicrafts. Objectives this project are to design a centre that can atrract tourist. To create a comfort table space requirement, to gives the best services, facilities and products. Location of this project at Jalan Hutan Kampong,Kepala Batas. The concept is Exploration through the journey of Kedah. The concept is to shown identity of Kedah. Kedah identity applied with carving and motive of Kedah.